THE STRATEGY OF INNOVATION DEVELOPMENT OF UKRAINE IN THE CONTEXT OF EU INTEGRATION - Makohon, Yuriy; Medvedkina, Yevheniya (Journal of European Economy, 2017)
The authors discuss the issues of improving and increasing the effectiveness of state policy in the area of international science and technology cooperation of Ukraine taking into consideration the integration priorities of the state, including the interactions with the EU.